Experiment of Processing Jackfruit Bean Flour in Making Pukis Cake - Yuliana Corlina (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Ampat Yogyakarta, 2022)
The purpose of this research is to test whether jackfruit seed flour is worthy of being an additive or a substitute ingredient in making pukis cakes in terms of colour, texture, taste, and aroma when compared to flour-based pukis cakes. This research is experimental quantitative research where the data analysis method is the sensory test and hedonic test. The results of the sensory test colour indicator using 50% wheat flour & 50% jackfruit seed flour (per cent preference test score 2.93 = 88% like), based on texture indicators (per cent preference test score 3.03 = 91% like), based on taste indicators (per cent liking test score 3.1 = 93% like), based on the aroma indicator (per cent liking test score 3.03 = 91% like). The results of the research on the use of 100% jackfruit seed flour in making pukis cake on colour indicators using sensory tests (per cent preference test score 2.73 = 82% likes), based on texture indicators using sensory tests on pukis cakes 100% jackfruit seed flour (per cent preference test scores 2.9 = 87% likes), the taste indicator uses a sensory test on pukis cake 100% jackfruit seed flour (per cent preference test score 3 = 90% likes). The aroma indicator uses a sensory test on pukis cake with 100% jackfruit seed flour (per cent preference test score 2.96=89% like).